2021
DOI: 10.21203/rs.3.rs-1151131/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Production and Characterization of Animal Waste Reinforced Composite Materials By Powder Metallurgy

Abstract: Boron carbide is a product used for reinforcement in composite production and frequently used in the defense industry. The fact that boron carbide behaves similarly to the mechanical properties of bone and that titanium is strengthened with boron carbide, which is used as a biomaterial, causes it to be preferred among composite materials. It also makes it attractive to use in industrial applications at high temperatures. It is known that Fe-B4C composites are used together with Fe matrix materials to improve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…Yonetken and Erol [18] fabricated Al-based composites reinforced with 3, 6, 9, 12, and 15% of BN by conventional microwave sintering at 550 • C. They reported the formation of compounds between the Al matrix and the BN reinforcement. Their study showed that the highest microhardness of 42.65 HV was observed in the case of Al at 12% BN, while the highest density of 2.975 g/cc was observed in the case of Al at 3% BN.…”
Section: Introductionmentioning
confidence: 99%
“…Yonetken and Erol [18] fabricated Al-based composites reinforced with 3, 6, 9, 12, and 15% of BN by conventional microwave sintering at 550 • C. They reported the formation of compounds between the Al matrix and the BN reinforcement. Their study showed that the highest microhardness of 42.65 HV was observed in the case of Al at 12% BN, while the highest density of 2.975 g/cc was observed in the case of Al at 3% BN.…”
Section: Introductionmentioning
confidence: 99%
“…Bu özellikler alüminyumu nano BN ile güçlendirmek için önemli bir malzeme yapmaktadır [33]. Ayrıca nano BN takviyeli metal matrisli kompozitler; kıvılcım plazma sinterleme, sıcak haddeleme ve döküm gibi yüksek sıcaklık teknikleri kullanılarak üretilebilmektedir [34][35][36][37][38]. Nano BN incelendiğinde, hegzagonal BN'ın (h-BN) içyapısı [39] görülebilir.…”
Section: Introductionunclassified